PERLINDUNGAN RAHASIA DAGANG DALAM HUBUNGANNYA DENGAN PERJANJIAN KERJA - Syarifa Mahila (Jurnal Ilmiah Universitas Batanghari Jambi, 2010)
Issues regarding trade secrets is very urgent in the field of smoothness and continuity of a business. Maintaining confidentiality of information must be done by the owner of confidential information by performing the steps appropriate and inappropriate. This means that all the steps that includes measures of fairness, decency, and propriety that must be done. Maintenance is usually confidential relations between workers and employers who are owners of trade secrets. In the work environment needs to be regulated company procedures that can ensure the confidentiality of information. It should be clearly and firmly regulated also in the company regulations regarding the party responsible for the information confidential. Trade secret is protected by the Act in line with the birth-related information and begin to function in economic activity.Keyword :  Trade Secrets, Employment Agreement, Economic Activities